Measuring Adherence to Hepatitis C Direct-Acting Antiviral Medications: Using the VAS in an HCV Treatment Clinic. Issue 1 (January 2018) - Burton, Mary Jane; Voluse, Andrew C.; Patel, Amee B.; Konkle-Parker, Deborah
Abstract : Objectives: To implement the widespread treatment of hepatitis C virus (HCV), validated self-report measures to assess medication adherence are needed for monitoring patients who are prescribed HCV direct-acting antivirals (DAAs). The Visual Analog Scale (VAS) is an efficient and well-validated tool for measuring adherence to antiretrovirals in human immunodeficiency virus populations. This study compared VAS scores with pill counts and serum levels of HCV RNA in a sample of HCV-infected veterans prescribed DAAs. Methods: Veterans initiating HCV DAAs were offered enrollment in our study. HCV treatment was prescribed in accordance with the standard of care. Follow-up study visits were scheduled every 28 days for a total of 12 weeks. Adherence to DAAs was assessed at weeks 4, 8, and 12 using pill counts and the VAS score. Serum levels of HCV RNA were measured at baseline, week 4 of DAA therapy, and week 12 (Ampliprep/Taqman, lower limit of quantification 43 IU/mL). Results: Between May 2013 and December 2014, 30 veterans were enrolled. Mean adherence via pill count at weeks 4, 8, and 12 (96.2%, 95.2%, and 98.2%, respectively) was nearly identical to the mean VAS scores (96.2%, 96.0%, and 98.2%, respectively). Wilcoxon signed rank tests demonstrated no differences between each VAS and pill count pair. The VAS score inversely correlated with HCV viral load 4 weeks after DAA initiation ( r −0.98) and at 12 weeks of treatment ( r −0.97). Conclusions: The VAS score compared favorably with objective measures of adherence. If future studies confirm our results, then the VAS will provide a simple and reliable method of assessing adherence to HCV DAAs in real-world treatment clinics. Abstract : Adherence to direct-acting antiviral medications is crucial to the successful treatment of chronic hepatitis C virus (HCV) infection. Validated tools for quickly assessing adherence to direct-acting antivirals in HCV clinics are lacking; therefore, the authors compared the Visual Analog Scale with objective measures of adherence in a real-world HCV treatment clinic.